2002
DOI: 10.1002/etc.5620210527
|View full text |Cite
|
Sign up to set email alerts
|

Modification of an ecotoxicological rating to bioassess small acid mine drainage‐impacted watersheds exclusive of benthic macroinvertebrate analysis

Abstract: The modified ecotoxicological rating (METR) approach to synthesizing integrative bioassessment data into a single number ranging from 0 to 100 was found to differentiate between multiple levels of impacts from acid mine drainage (AMD). Our objective was to develop a more cost-effective and time-efficient bioassessment technique than previously used in other large scale ecotoxicological ratings (ETRs) by minimizing the number of parameters required to rank stations to only those most descriptive of the benthic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 32 publications
0
4
0
1
Order By: Relevance
“…Sediments in that study were found to have high percentage water content, and it was suggested that pore‐water concentrations of free Fe ions in association with acidic pH were the likely source of toxicity [10]. In addition, Schmidt et al [40] found that sediment toxicity tests utilizing D. magna or Chironomus tentans , a sediment‐dwelling dipteran, were not predictive of benthic macroinvertebrate community responses to Al‐ and Fe‐dominated AMD seepage or sediments.…”
Section: Discussionmentioning
confidence: 99%
“…Sediments in that study were found to have high percentage water content, and it was suggested that pore‐water concentrations of free Fe ions in association with acidic pH were the likely source of toxicity [10]. In addition, Schmidt et al [40] found that sediment toxicity tests utilizing D. magna or Chironomus tentans , a sediment‐dwelling dipteran, were not predictive of benthic macroinvertebrate community responses to Al‐ and Fe‐dominated AMD seepage or sediments.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, the Leviathan dataset provides an important case history in establishing the success of acid mine drainage remediation activities. The use of biomonitoring as an indicator of ecological toxicity and mining‐related pollution impacts and improvements has been substantiated through studies that show close correlation of bioassessment metrics with the standard bioassays using specific test organisms, and with dissolved metal contaminant concentrations (Schmidt et al ; Griffith et al ). Studies combining controlled exposure of natural assemblages to metals and field manipulations of metal oxides on substrates have been used to detail recovery potential of different taxonomic groups (Cadmus et al ).…”
Section: Discussionmentioning
confidence: 99%
“…SQT 法最早由 Long 和 Chapman [4] 提出,它由沉积物化学,沉积物毒性测试以及底栖生物群落结构这 3 个 互补基元构成。 尽管这些基元单独使用时能提供有关环境胁迫的效应信息 [5] ,但均不能回答沉积物是否受 到污染、污染原因及程度等问题。 因此,上述三基元的结果必须予以集成,综合考虑各种数据信息所反映的环 境质量、污染程度以及数据信息之间的相关性来评价环境胁迫可能产生的潜在风险,这同时也是一种证据权 重评价,是生态风险评价的一个分支 [6鄄 8] ,SQT 以适当的信息简化,数据降维工具将各种沉积物质量信息通过 最佳专业评判( best professional judgment,BPJ) 转化为确定性的评价结果 [9] [10] 。 基于潜在环境胁迫的作用对象、暴露途径及预期的生物效应类型等方面的考虑,可通过增加、替换或 改进上述三基元的方式,加强 SQT 的生态相关性 [11] 。 7 6 5 4 摇 14 期 摇 摇 摇 吴斌摇 等:沉积物质量评价" 三元法冶 及其在近海中的应用 摇 基元构成的变化被认为是一种新的、增强型 SQT 法的再造 [12] 。 目前,通过引入生物放大、组织残毒、毒性 鉴定评估( toxicity identification evaluations,TIEs) 等基元,使评价结果可靠性得到进一步提升。 通常,沉积物化 学、毒理是 SQT 基元构成的必要组成部分,底栖生物群落结构则可替换为其他的基元。 此外,也有研究将特 定的生物有效性 [13] 或毒性参数纳入沉积物化学基元 [14] ,作为独立的证据权重水平。 当然,也可重新定义 SQT 的 3 个基本单元,选择适当的参数,纳入生物富集、慢性毒性试验等新的证据权重水平从而形成一种新型 的 SQT [12] 。 所有的附加基元均是根据具体的评价目标而纳入考虑,它们与传统的三基元具有同样的独立地 位。 目前,已经出现超过 14 种附加基元 [15] ,而纳入生物放大的 SQT 更成为当前标准的组成架构 [16] SQT 是一种通过集成多重证据水平,协调其间不一致的综合评价方法 [17] 。 其评价关键过程是将复杂的 沉积物数据转化为相对简单的评价结果和确定性结论,而这有赖于证据权重法,即基于所有可获得的信息及 其内部关系得出确定性结论的方法 [18] ,它包括不同权重水平的数据质量、程度以及一致性评价 [19] 。 SQT 以 及其他的证据权重评价方法包括定性和定量两大类解译工具 [8] ,前者是以简单方式,结合诸多证据水平,得 [16] , Chapman 和 MacDonald [6] [25] 以及模糊逻辑 [26] 以及节点分析 [27] [17] 。 指数法丢失了大量信息,可能得出误导性的结果。 因此,使用指数必须在适当的条件之下,且需要结合统计分析等其他手段一起使用。 综合评价指数并不乏应用实例,如 Carr [33] 构建了针对传统的三基元的总等级指数,以比较 Galveston 湾不 同站位沉积物环境质量。 Wildhaber 和 Schmitt [34] 提出危害排序指数,分别求得沉积物化学、毒理和底栖生态 3 个基元各自相对沉积物质量基准、毒性试验对照组毒性阈值的指数以及底栖生物群落的平均耐污度,进而以 相同权重计算三者的算术平均指数。 Cherry 等 [35] 则结合 Soucek 等 [36] 提出的参数筛选方法,分别筛选物理、 化学、毒理、生态等基元中的参数,构架了生态毒理等级指数;Schmidt 等 [37] 通过线性回归、双变量相关分析以 及单因素方差分析等手段选取最能反映底栖生物响应的参数,对上述指数进行了修正,提出了改进的生态毒 理等级指数。 生态毒理等级指数最初是用于评估采矿点源污染等造成的水体沉积物质量恶化, 而 Locke 等 [38] 将其引入维吉尼亚州 Clinch 河的非点源污染引起的沉积物质量变化评价。 此外,Semenzin 等 [28] 采用多 标准决策分析法,结合生物有效性以及生态、毒理提出了综合效应指数;Usero 等 [31] 则提出了一种沉积物质量 综合指数,用于概述沉积物环境的主要特征并用于不同沉积物环境质量的比较。 [41] ,但 SQT 通过结合专家评判的逻辑体系,很好的解决了这些问题。 SQT 的适用对象从最初的海洋沉积...…”
Section: 摇 研究进展unclassified